Diagnose Expert System Dental Disease In Humans Method Using Dempster Shafer - Etiani Bu'ulolo; Fricles Ariwisanto Sianturi (Journal of Computer Networks, Architecture and High Performance Computing, 2020)
Dental disease is one of the many health problems Complained of by the people of Indonesia. Dental health is a reflection of human health. Lack of knowledge and limited sources of information on oral health have the caused public awareness to maintain oral and dental health is still low .. The development of one of the fields of information technology namely artificial intelligence has been Widely applied in various fields of life can be used as a solution to Overcome this problem. In this study, the dental and oral disease expert system uses the Dempster Shafer method to control inferences that Contain thought patterns and reasoning mechanisms used by experts in solving problems.